1993
DOI: 10.1002/hep.1840170612
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of body water in patients with cirrhosis: The effect of liver transplantation

Abstract: We compared total body water and intracellular-extracellular distribution of body water between male patients with mild liver disease without ascites (n = 9), male patients with severe liver disease and gross ascites (n = 6) and a group of age-, sex-, height- and weight- matched controls (n = 6). In addition, we documented the effects of liver transplantation on intracellular, extracellular and total body water in 12 patients (6 men and 6 women) by means of deuterium oxide dilution and whole-body potassium cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…A preliminary study aimed at establishing the time needed by 2H,0 and Br to reach equilibrium was done on the plasma of five unselected cirrhotic patients. Both tracers reached equilibrium 2.5 h after their administration, a time similar to that for healthy subjects and very close to that obtained by others for TBW (McCullough et al 1991 ;Prijatmoko et al 1994;Zillikens et al 1992a) and ECW (Crawford et al 1993;McCullough et al 1991) of nonascitic cirrhotics. Following this finding, blood samples for 'H,O and Br measurements were taken just before the tracer load and 3-5 h later in both cirrhotic and control subjects.…”
Section: Subjectssupporting
confidence: 89%
See 1 more Smart Citation
“…A preliminary study aimed at establishing the time needed by 2H,0 and Br to reach equilibrium was done on the plasma of five unselected cirrhotic patients. Both tracers reached equilibrium 2.5 h after their administration, a time similar to that for healthy subjects and very close to that obtained by others for TBW (McCullough et al 1991 ;Prijatmoko et al 1994;Zillikens et al 1992a) and ECW (Crawford et al 1993;McCullough et al 1991) of nonascitic cirrhotics. Following this finding, blood samples for 'H,O and Br measurements were taken just before the tracer load and 3-5 h later in both cirrhotic and control subjects.…”
Section: Subjectssupporting
confidence: 89%
“…Water retention is common in the later stages of liver cirrhosis (Schober et al 1979;McCullough et al 1991;Zillikens et al 1992a;Crawford et al 1993;Prijatmoko et al 1994). The increase in TBW is largely due to an expansion of extracellular water (ECW;McCullough et al 1991 ;Crawford et al 1993) which may become clinically apparent in the form of oedema or ascites. However, ICW may be expanded also and contribute to the overall increase in TBW (Schober et al 1979).…”
mentioning
confidence: 99%
“…9 However, in situations where there are clinically important changes in the intracellular and extracellular distribution of water, such as cirrhosis, the value of single-frequency BIA is limited. 3,10,11 Previous studies have indicated an improved prediction of body water compartments by BIA if measurements are made while the frequency of the applied current is changed. [12][13][14] At low frequencies, the current passes through the extracellular fluids because of the capacitance effect of cell membranes and tissue interfaces, whereas at higher frequencies, the current is conducted through both the intra-and extracellular fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Single‐frequency BIA is a safe, non‐invasive, rapid, and inexpensive method of assessing total body water (TBW) in healthy individuals 9 . However, in situations where there are clinically important changes in the intracellular and extracellular distribution of water, such as cirrhosis, the value of single‐frequency BIA is limited 3,10,11 . Previous studies have indicated an improved prediction of body water compartments by BIA if measurements are made while the frequency of the applied current is changed 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that significant changes in body compartments occur in patients with cirrhosis 9 . These patients have altered body water compartments 10,11 . Some authors have reported an increase in body water even before ascites and edema are obvious 11,12 .…”
Section: Introductionmentioning
confidence: 99%